The polyunsaturated fatty acids and skin health in horses - Goh, Yong Meng; Sia, Juo Yiing; Goriman Khan, Mohd Azam Khan (Universiti Putra Malaysia Press, 2004)
This paper highlighted the importance and contribution of PUFAs (polyunsaturated fatty acid) and their metabolites to the skin health of horses. PUFAs are the major constituents of cellular membrane and regulates membrane fluidity as well as normal skin growth. These are achieved through the presence and balance of their metabolites, which incidentally possess unique anti-inflammatory and/or pro-inflammatory properties. The understanding of the roles and balance of these fatty acids offered an additional approach in the management of skin health in horses.